Complete molecular spectrum of β-globin gene mutations via direct sequencing identifies seven novel variants in β-thalassemia major - Torin Abdulaziz Sadoon; Hemin Esmael Othman (PLoS ONE, 2025)
Background A common monogenic condition, β-thalassemia, is caused by a variety of mutations in the β-globin ( HBB ) gene. It is essential to accurately characterize these mutations for genetic counselling, diagnosis, and treatment. Objective This study aimed to characterize and provide an updated and complete molecular spectrum of β-globin gene mutations, including both known and novel mutations, estimate their frequencies, and determine their possible deleterious effects. Methods A total of 60 major β-thalassemia patients who sought treatment at Jeen Hospital in Duhok from August 2024 to February 2025 were analyzed using direct DNA sequencing of the β-globin gene. Results Out of 60 sequence chromatograms, 40 were of excellent quality. Among these, 26 distinct mutations were found, comprising 10 exonic and 16 intronic variants. The most prevalent benign variants were IVSII-16 G > C (80%) and IVS II-666 C > T (77.5%), followed by Cd2 T > C [HBB:c.9 T > C, (62.5%)]. The pathogenic exonic mutations were found in coding regions, including Cd5 -CT [HBB:c.17_18delCT, (17.5%)], Cd6 A > T [HBB:c.20A > T (sickle cell mutation, 2.5%)], Cd8 A > G [HBB:c.26A > G (2.5%)], Cd39 C > T [HBB:c.118C > T, (5%)], Cd44 C > T [HBB:c.134C > T, (2.5%)], and Cd44 -C [HBB:c.135delC, (2.5%)]. Pathogenic intronic variants were also documented in splice junctions, including IVS I-1 G > A (15%) and IVS I-5 G > C (17.5%). Notably, seven novel variants were detected in this study, including four intronic variants (IVS I-129 + C Ins, IVS II-72 G > A, IVS II-579 G > A, and IVS II-763 + C Ins) and three exonic variants [Cd44 C > T (HBB:c.135C > T), Cd47 –G (HBB:c.142delG), and Cd118 –TT (HBB:c.355_356delTT)]. The majority of which were expected to be pathogenic or likely pathogenic based on variant location, predicted functional effect, and observed frequencies. Conclusion The molecular investigation of β-thalassemia patients in Duhok showed a significant level of genetic variability in the β-globin gene and a high prevalence of compound heterozygosity among the β-thalassemia patients. The finding of several new variants is significant since it adds to the current mutation database and broadens the known mutational spectrum of the β-globin gene in this community. It also supports the necessity of thorough molecular diagnostics in regional management, screening, and genetic counseling of β-thalassemia.